Investigation of static and dynamic bulk moduli in a carbonate field. Issue 1 (2nd January 2021) - Sharifi, Javad; Saberi, Mohammad Reza; Javaherian, Abdolrahim; Hafezi Moghaddas, Naser
Abstract : Bulk modulus which relates seismic attributes to rock and fluid properties is considered as an important parameter for seismic reservoir characterisation workflows, and can provide useful information for such studies. However, its measurement and modelling approaches are yet to be sufficiently addressed and discussed especially for carbonate rocks. In this research, in order to provide more information about bulk modulus, nine samples from a carbonate oilfield were subjected to static and dynamic investigations under dry and saturated conditions. Then, the dynamic modulus was calculated using well log data and ultrasonic measurements. In order to obtain static data, multi-stage triaxial compression tests were performed on the vertical plugs extracted from conventional cores taken at different selected depths. The results showed that static and dynamic bulk moduli follow similar trends, although the value of dynamic modulus is usually higher. Furthermore, several empirical relationships based on simple linear regression and forward and backward stepwise multiple linear regressions were developed to relate measured static and dynamic bulk moduli for the given field, then proposed equations were evaluated by ANOVA analysis. Besides, dry and saturated bulk moduli were modelled using Xu and Payne rock physics model. Here, saturated bulk modulus was modelled using either dynamic or static dry bulk moduli within the Gassmann's theory. It is observed that Gassmann's equation gives a more accurate result using dynamic data rather than static ones. The poor Gassmann's equation prediction under static condition could be attributed to microcracks in the samples and the uncertainty associated with this theory for complex pore geometry. The outcomes of this study can, furthermore, provide the necessary information and relationships for rock physics (e.g. shear wave estimating and fluid substitution modelling) and geomechanical (e.g. CO2 injection and compaction forecast) studies for exploration and development programs.